Fast ultrasound assisted synthesis of chitosan-based magnetite nanocomposites as a modified electrode sensor. (20th October 2016) - Freire, T.M.; Dutra, L.M.U.; Queiroz, D.C.; Ricardo, N.M.P.S.; Barreto, K.; Denardin, J.C.; Wurm, Frederik R.; Sousa, C.P.; Correia, A.N.; de Lima-Neto, P; Fechine, P.B.A.
Graphical abstract: Highlights: In situ and fast synthesis of magnetic nanoparticles on chitosan by sonochemistry. All samples presented superparamagnetic behavior. Hybrid nanocomposite available for use as modified electrodes. Abstract: Chitosan-based magnetite nanocomposites were synthesized using a versatile ultrasound assisted in situ method involving one quick step. This synthetic route approach results in the formation of spheroidal nanoparticles (Fe3 O4 ) with average diameter between 10 and 24 nm, which were found to be superparamagnetic with saturation magnetization (Ms) ranges from 32–57 emu g −1, depending on the concentration. The incorporation of Fe3 O4 into chitosan matrix was also confirmed by FTIR and TG techniques. This hybrid nanocomposite has the potential application as electrochemical sensors, since the electrochemical signal was excepitionally stable. In addition, the in situ strategy proposed in this work allowed us to synthesize the nanocomposite system in a short time, around 2 min of time-consuming, showing great potential to replace convencional methods. Herein, the procedure will permit a further diversity of applications into nanocomposite materials engineering.